2007
DOI: 10.1016/j.canlet.2006.09.007
|View full text |Cite
|
Sign up to set email alerts
|

BRAF and KRAS gene mutations in intraductal papillary mucinous neoplasm/carcinoma (IPMN/IPMC) of the pancreas

Abstract: The Raf/MEK/ERK (MAPK) signal transduction is an important mediator of a number of cellular fates including growth, proliferation and survival. The BRAF gene is activated by onogenic RAS, leading to cooperative effects in cells responding to growth factor signals. Our study was performed to elucidate a possible role of BRAF in the development of IPMN (Intraductal Papillary Mucinous Neoplasm) and IPMC (Intraductal Papillary Mucinous Carcinoma) of the pancreas. Mutations of BRAF and KRAS were evaluated in 36 IPM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 39 publications
4
83
0
Order By: Relevance
“…[18][19][20][21][22] Consistent with previous studies, the prevalence of KRAS mutations in IPMNs was 67%. In contrast, only 14% of MCNs harbored a KRAS mutation.…”
Section: Discussionsupporting
confidence: 89%
“…[18][19][20][21][22] Consistent with previous studies, the prevalence of KRAS mutations in IPMNs was 67%. In contrast, only 14% of MCNs harbored a KRAS mutation.…”
Section: Discussionsupporting
confidence: 89%
“…However, targeting the B-Raf kinase isoform appears to be most effective when activating mutations are present in cancer cells, such as the reported V600E Raftype mutation in thyroid cancer and melanoma (27,37). In our study, we investigated the effects of a small-molecule inhibitor to Raf and VEGFR2 on pancreatic cancer cells, although the Raf signaling cascade in this cancer entity is predominantly activated via KRAS (10), an oncogene known to be mutated in >90% of pancreatic adenocarcinomas (38,39). Indeed, we found that inhibition of Raf led to a potent reduction in MEK, Erk, and STAT3 activation in cancer cells, suggesting that the Raf pathway represents a valid molecular target in this cancer entity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, frequent mutations of KRAS have been previously detected in the pancreatic juice, tissues and EUSFNAs of patients with PDAC and IPMN (SUPPLEMENTARY TABLE 1 [supplementary material can be found online at www.informahealthcare.com/suppl/10.1586/14737159.2015.1002771_Suppl). Interestingly, the frequency of mutated KRAS remains consistent as IPMN progresses (i.e., from adenoma to carcinoma) [13]. However, KRAS mutations have been shown to have high specificity, but low sensitivity for mucinous differentiation (100-96% and 54-45%, respectively) [14,15].…”
Section: Expert Commentary and Five-year Viewmentioning
confidence: 99%